Inhibitive effect of cefuroxime on the corrosion of mild steel in hydrochloric acid solution - Singh A.K.; Quraishi M.A.; Ebenso E.E. (My University, 2025)
The corrosion inhibition properties of cefuroxime (CFM) for mild steel corrosion in HCl solution was investigated using electrochemical impedance spectroscopy (EIS), potentiodynamic polarization and gravimetric methods. Mixed mode of adsorption (physisorption and chemisorption) is proposed for the inhibition and the process followed the Langmuir adsorption isotherm. The mechanism of adsorption inhibition and type of adsorption isotherm were proposed from the trend of inhibition efficiency with temperature, E a and ΔG° ads. Potentiodynamic polarization study clearly revealed that CFM acted as mixed type inhibitor but predominantly cathodic. The experimental data showed a frequency distribution and therefore a modelling element with frequency dispersion behaviour and a constant phase element (CPE) have been used. © 2011 by ESG.